Biconcave micro-optofluidic lens with low-refractive-index liquids - Song, Chaolong (2012)
One of the current problems of micro-optofluidics is the choice of a suitable liquid with a high refractive index (RI). We report the use of a low-RI liquid in a biconcave liquid-core liquid-cladding lens for focusing light. For the characterization of the lens, a telescope system was constructed from polydimethylsiloxane lenses to collimate and expand a light beam emitted from an optical fiber. The tunable optofluidic biconcave lens focuses the parallel beam. Fluorescent dye diluted in an index-matching liquid was used for the visualization of the light rays in a beam-tracing chamber. The focused beam is tuned by adjusting the flow rate ratio between core and cladding streams.